Penerapan strategi pembelajaran relating, experiencing, applying, cooperating, transferring (react) untuk meningkatkan keterampilan pemecahan masalah soal cerita matematika peserta didik kelas iv sekolah dasar - Riska Mustikaningrum; Hadi Mulyono; Siti Kamsiyati (Didaktika Dwija Indria, 2019)
The purpose of this research was to improve mathematical word problems solving skills through the use of REACT strategy in IV grade students at SDN Soropadan No. 108 Surakarta in the 2018/2019 academic year. This study was a Classroom Action Research (CAR), which consisted of 2 cycles and each cycle was held in two confluences. The subjects of this research were teacher and students in IV grade, which amounted to 37 students. Observation, interview, test, and documentation were used as the data collecting techniques. The data validity techniques were content validity and technical triangulation. The data analysis techniques were descriptive comparative, critical analysis, and interactive analysis model Miles & Huberman. The result of this research showed that the average score of mathematical word problems solving skills on pre-action was 36,04 with 2,7% of classical completeness. The average score of first cycle was 68,69 with 51,35% of classical completeness. The average score of second cycle was 85,54 with 83,78% of classical competeness. It concluded that the REACT strategy can improve mathematical word problems solving skills in IV grade students at SDN Soropadan No. 108 Surakarta in the 2018/2019 academic year.Keyword: mathematical word problems solving skills, REACT strategy.